Simulated physiological oocyte maturation has side effects on bovine oocytes and embryos - Razza, Eduardo M. [UNESP] (2019)
Purpose: Oocyte maturation is a complex process involving nuclear and cytoplasmic modulations, during which oocytes acquire their ability to become fertilized and support embryonic development. The oocyte is apparently “primed” for maturation during its development in the dominant follicle. As bovine oocytes immediately resume meiosis when cultured, it was hypothesized that delaying resumption of meiosis with cyclic nucleotide modulators before in vitro maturation (IVM) would allow the oocytes to acquire improved developmental competence. Methods: We tested the Simulated Physiological Oocyte Maturation (SPOM) system that uses forskolin and 3-isobutyl-1-methylxanthine for 2 h prior to IVM against two different systems of conventional IVM (Con-IVM). We evaluated the ultrastructure of matured oocytes and blastocysts and also assessed the expression of 96 genes related to embryo quality in the blastocysts. Results: In summary, the SPOM system resulted in lower blastocyst rates than both Con-IVM systems (30 ± 9.1 vs. 35 ± 8.7; 29 ± 2.6 vs. 38 ± 2.8). Mature SPOM oocytes had significantly increased volume and number of vesicles, reduced volume and surface density of large smooth endoplasmic reticulum clusters, and lower number of mitochondria than Con-IVM oocytes. SPOM blastocysts showed only subtle differences with parallel undulations of adjacent trophectoderm plasma membranes and peripherally localized ribosomes in cells of the inner cell mass compared with Con-IVM blastocysts. SPOM blastocysts, however, displayed significant downregulation of genes related to embryonic developmental potential when compared to Con-IVM blastocysts. Conclusions: Our results show that the use of the current version of the SPOM system may have adverse effects on oocytes and blastocysts calling for optimized protocols for improving oocyte competence.